ELECTIONS - AN IMPORTANT CRITERION OF CIVIL SOCIETY - Shayusupova Munisa Shaniyazovna (Journals Park Publishing, 2023)
This article reveals the role of democratic elections in the formation of civil society. The content, nature and significance of the elections are explained. It also analyzes the description of civil society, its institutions and their participation in elections. Proposals and recommendations have been put forward for further improvement of the Electoral Code of the Republic of Uzbekistan.
Keywords: elections, democracy, civil society, civil society institutions, political parties, non-governmental non-profit organizations.